2017
DOI: 10.18203/2349-3933.ijam20174289
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of clinical, biochemical and radiological features in pancreatitis

Abstract: Background: Pancreatitis is quite common problem, it may present either as abdominal emergency with fulminant course or as an indolent process leading to long-term medical as well as surgical complications often leading to poor prognosis if not intervened timely.Methods: The present study conducted in the department of medicine, Dr. S. N. medical college, Jodhpur. Participants after understanding the study protocol and procedure, asked to give their written consent for the study. A cross sectional hospital bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The mean age of the study population in years was 44.46±9.16 correlated to a study conducted by Bhimwal et al [1] that out of a total of 50 cases, the maximum cases were of age group 30-39 years (32.5%) followed by 25% in the age group of 50-59. In a study by Balaji et al [2], the mean age of the patients was 45.4 years (range 30-69 years).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mean age of the study population in years was 44.46±9.16 correlated to a study conducted by Bhimwal et al [1] that out of a total of 50 cases, the maximum cases were of age group 30-39 years (32.5%) followed by 25% in the age group of 50-59. In a study by Balaji et al [2], the mean age of the patients was 45.4 years (range 30-69 years).…”
Section: Discussionsupporting
confidence: 81%
“…Bhimwal et al [1] study reported that previous history of abdominal pain in all cases is present, followed by epigastric pain (90%), nausea and vomiting (80%), weight loss (60%), fever (30%), diarrhea (30%) and diabetes (20%) of cases. 92.5% (37) of cases were mild, and 7.5% (3) were severe acute pancreatitis.…”
Section: Discussionmentioning
confidence: 95%
“…Pancreatitis is characterized as a pancreatic inflammatory condition that may or may not impact nearby tissues or distant organ systems [1]. The histology may return to normal between attacks or it may manifest as a solitary attack that recurs in discrete episodes [2,3].…”
Section: Introductionmentioning
confidence: 99%